2012
DOI: 10.4172/2155-6105.s4-002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex and Gonadal Hormones on Cocaine and Food Reinforcement Paradigms

Abstract: IntroductionWomen, compared to men, face a more severe pattern of cocaine dependence. Sex differences in the profile of cocaine dependence have indicated that women, relative to men, transition faster from first use to entering treatment [1], which may be explained by women abusing cocaine via more addictive routes more quickly and reporting a more rapid progression of drug dependence [2]. In addition, cocaine dependent women report shorter cocaine-free periods [3], have an increased incidence of relapse [4], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 85 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…The females that choose cocaine also do this sooner than the males that ultimately choose cocaine (Perry et al 2013b). Other investigators have also shown that more females choose cocaine over a food reinforce compared with males (Kerstetter et al 2012; Kerstetter and Kippin 2011). …”
Section: Sex Differences In Animals Models Of Addictionmentioning
confidence: 93%
See 1 more Smart Citation
“…The females that choose cocaine also do this sooner than the males that ultimately choose cocaine (Perry et al 2013b). Other investigators have also shown that more females choose cocaine over a food reinforce compared with males (Kerstetter et al 2012; Kerstetter and Kippin 2011). …”
Section: Sex Differences In Animals Models Of Addictionmentioning
confidence: 93%
“…In these studies animals are considered to exhibit addiction-like behavior if they continue to take a drug when receiving an aversive mild shock, exhibit high levels of responding on a progressive ratio schedule, and continue to respond for the drug under conditions when drug is not available. A few studies have examined the proportion of female rats that develop addiction-like behavior in the laboratory; in these studies where males and females are allowed to choose cocaine or a food reward, more females than males choose cocaine and females exhibit higher responding for cocaine than do males (Perry et al, 2013b;Kerstetter et al, 2012;Kerstetter and Kippin, 2011).…”
Section: Sex Differences In Animals Models Of Addictionmentioning
confidence: 99%
“…In contrast to the pain literature, sex differences in addiction are well documented, although not always in the same directions when comparing rats, mice and humans (Anker and Carroll, 2011; Kerstetter and Kippin, 2011). In a test of conditioned habit formation for a food reward (Quinn et al , 2007), XX (all studies in the MF1 FCG) mice regardless of gonadal sex formed the habit more quickly than XY mice.…”
Section: Sex Chromosomes and Behaviormentioning
confidence: 94%
“…Female rats exhibit enhanced responding to psychostimulants in multiple paradigms in a manner both dependent and independent of ovarian sex hormones (Hu et al 2004;Jackson et al 2006). In ovariectomized rats, E 2 enhances the sensitization of cocaine-induced locomotor behavior and CPP (Segarra et al 2010), self-administration of cocaine on both fixed and progressive ratio schedules of reinforcement (Lynch and Taylor 2005;Zhao and Becker 2010), and preference for cocaine over food reinforcement in a discrete trials procedure (Kerstetter and Kippin 2011), and lowers thresholds for electrical brain stimulation of the ventral tegmental area (Galankin et al 2010). Thus, E 2 -enhanced expression of CPP could be interpreted as further evidence in females of "enhanced abuse liability to cocaine," yet this interpretation is at odds with the finding that E 2 also enhanced extinction of drug seeking.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial literature supports that estrogens mediate the enhancement of drug seeking observed in females (Febo et al 2002;Larson et al 2007;Segarra et al 2010;Kerstetter and Kippin 2011), but little is known regarding the role of estrogens during treatment. Preclinically, treatment is modeled through extinction learning, which results in the formation of a new inhibitory memory that suppresses drug seeking Torregrossa and Taylor 2012).…”
mentioning
confidence: 99%